Branding Springbok rugby, branding the nation: memorial marketing and nation-building in post-apartheid South Africa - (:unkn) unknown (My University, 2024)
The Springbok brand invented by the South African national rugby team in 1906 was used for over 80 years as the symbol of a quintessentially white South Africa, with the animal even becoming a byword for its white athletes at the international level, for the country as a whole, and for its white citizens. When democracy came of age in the 1990s, most anti-apartheid activists wanted to give it the chop for having represented and served white minority rule, but Nelson Mandela, having understood its sacred nature for Afrikaners, whom he needed on his side during the political negotiations, saved it, turning it into a symbol of inclusion by wearing the green and gold jersey with the Springbok on the heart during the 1995 RWC world cup final. At a time when common ground was desperately needed to establish the New South Africa, the ‘all-white’ Springbok now miraculously stood for the Rainbow Nation. This chapter will look at the history of the Springbok brand in rugby and outside as fundamentally plastic, serving contingent, ever-changing nationalist and commercial purposes as one of the most identifiable representations of ‘South Africanness’, being currently used in the elaboration of an inclusive collective memory and in contemporary South Africa’s nation-branding effort to imagine itself.
Keywords: African Research